The experiences of depressed pregnant women participating in a cognitive behavioral therapy program via video communication: an exploratory qualitative study - Eunjoo Lee; Mijung Kim; Youngsuk Park (Korean Society of Women Health Nursing, 2022)
Purpose This study explored the experiences of pregnant women with depressed mood participating in a group cognitive behavioral therapy (CBT) program using video communication, based on Beck's cognitive theory. Methods The participants were six pregnant women out of 13 women who had participated in an 8-session group CBT program using video communication for women with depressed mood (Edinburgh Postnatal Depression score of ≥9). Data were collected from February 20 through March 25, 2021. In-depth individual interviews were conducted through a video conferencing platform at 1 month post-baseline. Thematic analysis was done. Results Three themes, 10 subthemes, and 38 concepts were derived from experiences of participating in the 4-week group CBT program (twice a week). The first theme, entitled "continuing realization" had subthemes of "a negative and instable self," "a selfish judgment that excludes others," and "a strong belief in self-control." The second theme, entitled "attempt to change for restoration" had subthemes of "shift to rational thinking," "freedom from suppressed beliefs," "tolerance of other people," and "courage for self-expression." The third theme, entitled "departure for a positive life," had subthemes of "emotional healing," "faith in oneself," and "reestablishing the criteria for happiness." Conclusion Pregnant women with depressed mood expressed that continuing realizations and attempts to change supported their transition toward a positive direction of healing. Thus, they were able to change their distorted thinking into rational thinking through CBT using video communication. These findings support the use of group CBT using video communication with pregnant women who have depressed mood.